2009
DOI: 10.1111/j.1438-8677.2009.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in efficient metabolite management and nutrient metabolic regulation between wild and cultivated barley grown at high salinity

Abstract: Physiological and biochemical responses of Hordeum maritimum and H. vulgare to salt stress were studied over a 60-h period. Growth at increasing salinity levels (0, 100, 200 and 300 mM NaCl) was assessed in hydroponic culture. H. maritimum was shown to be a true halophyte via its typical behaviour at high salinity. Shoot growth of cultivated barley was gradually reduced with increasing salinity, whereas that of wild barley was enhanced at 100 and 200 mm NaCl then slightly reduced at 300 mM NaCl. The higher sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
6
14
0
Order By: Relevance
“…These results are in agreement with those of Yousfi et al (2010) who reported better salt tolerance of this species as compared to H. vulgare. More importantly, our results point out that, contrarily to our expectations, mild salinity may be beneficial for the plant ability to cope with P deficiency stress.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with those of Yousfi et al (2010) who reported better salt tolerance of this species as compared to H. vulgare. More importantly, our results point out that, contrarily to our expectations, mild salinity may be beneficial for the plant ability to cope with P deficiency stress.…”
Section: Discussionsupporting
confidence: 93%
“…4, the calculated values (dashed lines) are in reasonable agreement with the observed ones, suggesting that the considered solutes were the main determinants of the leaf osmotic potential. Neverthless, Yousfi et al (2010) found that at 100 mM NaCl, Hordeum maritimum used inorganic solutes (such as Na ? ) for osmotic adjustment and kept organic solutes and a large part of K ?…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, drought reduced growth on a whole-plant FW and DW basis of both species, especially after withholding water for at least 14 d. Wild barley was less affected by drought than cultivated barley. Yousfi et al (2010) reported a similar response to salinity stress and related this behavior to the halophytic character of wild barley (Fig. 2).…”
Section: Discussionmentioning
confidence: 60%
“…Lamsi; Hessini et al, 2015), provided by the National Agronomy Institutes of Tunisia (INAT), and seeds of wild barley (Hordeum maritimum L.; Yousfi et al, 2010), collected from Soliman Sebkha (saline depression located 30 km south of Tunis, semi-arid area), were germinated on two layers of Whatman filter paper moistened with 10 mL sterile deionized water in the dark at 25°C. After 7 d, when the second leaves appeared, seedlings were transferred to 5-L plastic pots (100 pots with two plants per pot) filled with 5 kg of soil taken from the agricultural parcel at the Center of Biotechnology of Borj Cedria.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…In contrast, soluble carbohydrate concentrations increased with salt stress, indicating their contribution to osmotic adjustment (Yousfi et al . ). Assuming that 40.75 nmol·kg −1 of symplastic water corresponds to 0.1 MPa (Fricke & Peters ), the contribution of soluble sugar was lower and did not exceed 2.2% of osmotic adjustment, even with 200 m m NaCl.…”
Section: Discussionmentioning
confidence: 97%